ヒガシ ドロンイングモードランド,セール・ロンダーネ サンチ チガク チョウサタイ ホウコク 20112012(JARE-53) - 菅沼, 悠介; スガヌマ, ユウスケ; 金丸, 龍夫; カナマル, タツオ; 大岩根, 尚; オオイワネ, ヒサシ; 齋田, 宏明; サイタ, ヒロアキ; 赤田, 幸久; アカダ, ユキヒサ; Suganuma, Yusuke; Kanamaru, Tatsuo; et al. (2012)
P(論文) 第53次日本南極地域観測隊(JARE-53)夏隊の一部は,2011-2012年の夏期に,東ドロンイングモードランドのセール・ロンダーネ山地において地形・測地調査を実施した.また,この調査はBelgian Antarctic Research Expedition (BELARE)とInternational Polar Foundation(IPF)のサポートによって実施された.本調査のメンバー構成は,地形調査担当3名,測地担当1名,およびフィールドアシスタント1名である.南極への移動経路は往復路ともにドロンイングモードランド航空ネットワーク(DROMLAN)を利用し,空路ケープタウンからノボラザレフスカヤ基地滑走路を経由して現地入りした.調査地域はセール・ロンダーネ山地の西部および中部とした.本稿では調査,設営,気象をはじめとする本調査隊の行動全般について報告する. Geomorphologic and geodetic field surveys were carried out in the Sør Rondane Mountains, East Dronning Maud Land, Antarctica, during the 2011-2012 summer season as part of the 53rd Japanese Antarctic Research Expedition (JARE-53). The field party consisted of three geomorphologists, one geodesist, and one field assistant. The expedition was supported by the Belgian Antarctic Research Expedition (BELARE) and the International Polar Foundation (IPF). Dronning Maud Land Air Network (DROMLAN) provided air transport from Cape Town, South Africa to the Sør Rondane Mountains via Novolazarevskaya Airbase. The survey areas were the central and western parts of the Sør Rondane Mountains. This report summarizes the field expedition in terms of operations, logistics, and weather records. departmental bulletin paper